Akibat Hukum Sipalaiang (Kawin Lari) Pada Suku Mandar Menurut Undang-Undang Perkawinan - Baharuddin, Wahdaniah (Pusat Kajian Pesisir dan Masyarakat Hukum Adat Fakultas Hukum Universitas Pattimura, 2023)
Sipalaiang in the Mandar tribe according to the law. Sipalaiang is a social phenomenon carried out by some Mandar tribal peoples. Sipalaiang is considered the last resort for couples who are in love who want to get married, but because there are several factors that make it impossible, including not getting the blessing of one or both parties' parents or family. Purpose of the Research to provide an explanation of the meaning and legal consequences arising from sipalaiang marriage in the Mandar Tribe. The research method used is normative with a statutory approach and a conceptual approach. The sources of legal materials used are primary and secondary legal sources. The technique of collecting legal materials used in this study was through library research and reviewing some of the literature. The legal materials used were primary and secondary which were analyzed qualitatively and then presented descriptively. Results of the Research, sipalaiang in the Mandar custom is a culture of eloping by the Mandar tribe which means between a man and a woman who love each other and agree to build a household but are hindered by several factors so that the marriage is carried out without the presence of the family and a marriage like this can be said to be a disgrace, both for the families of both parties and those who carry out the silariang. As for the factors that influence sipalaiang, namely, there is no blessing from parents, against arranged forced marriages, the habits of some parents in finding a mate for their children and differences in social strata. Therefore, the marriage has legal consequences that can be canceled in accordance with the provisions of the applicable laws and regulations which are explained in Article 6 paragraph 1 of the Marriage Law.